2022
DOI: 10.3389/fpls.2022.1015652
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Cannabis Nutrition: Elevated root-zone phosphorus significantly increases leachate P and does not improve yield or quality

Abstract: Phosphorus (P) is an essential but often over-applied nutrient in agricultural systems. Because of its detrimental environmental effects, P fertilization is well studied in crop production. Controlled environment agriculture allows for precise control of root-zone P and has the potential to improve sustainability over field agriculture. Medical Cannabis is uniquely cultivated for the unfertilized female inflorescence and mineral nutrition can affect the yield and chemical composition of these flowers. P typica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…In the experiment from Westmoreland and Bugbee (2022) , there was no significant effect of P concentration in inflorescence yield or cannabinoid concentration, but significant differences in leachate P increasing 12-fold in response to the 3-fold increase in P fertilizer rate (25 to 75 mg P L −1 ). The authors suggested an optimum P supply of 25 mg P L −1 for continuous mineral fertilization.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In the experiment from Westmoreland and Bugbee (2022) , there was no significant effect of P concentration in inflorescence yield or cannabinoid concentration, but significant differences in leachate P increasing 12-fold in response to the 3-fold increase in P fertilizer rate (25 to 75 mg P L −1 ). The authors suggested an optimum P supply of 25 mg P L −1 for continuous mineral fertilization.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, promoting nutrient stress during flowering to enhance P re-mobilization and translocation seems to be a suitable strategy to increase P use efficiency and avoid excessive P fertilization. This is currently a relevant issue to decrease the environmental impact of medicinal cannabis cultivation ( Westmoreland and Bugbee, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, the findings suggest 35–70 mg L −1 Mg as the optimal concentration range for cannabis plant development and function. These results add understanding concerning effects of the macronutrient Mg, to the information available about effects of the three macronutrients N, P, and K on medical cannabis plants at the vegetative growth phase [ 8 , 13 , 14 ], and the reproductive growth phase [ 7 , 15 , 16 , 18 , 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 86%